Long-term Assessment of N2O Emission Factor in Full-scale Oxidation Ditch Reactor Considering Spatiotemporal Distribution - Otomo, Shohei; Terada, Akihiko; Li, Yu-You; Nishitoba, Kazuya; Takakai, Fumiaki; Okano, Kunihiro; Miyata, Naoyuki; Masuda, Shuhei (Journal of Water and Environment Technology, 2021)
In full-scale sewage treatment plants, long-term and high-frequency monitoring is required to mitigate nitrous oxide (N2O) emissions. In this study, the profile of the dissolved N2O concentration in a full-scale oxidation ditch reactor was investigated to determine the variation of the N2O emission factor. It was found that the concentration of dissolved N2O depended on microbial activity, which is affected by water temperature, dissolved oxygen concentration, and the dimensional relationship between the rotator and the inflow point. In the reactor, higher transcription levels of amoA mRNA and lower transcription levels of clade II type nosZ mRNA may be associated with N2O production. The emission factor for removed dissolved inorganic nitrogen presented a mean value of 0.86% and a median of 0.19%. When N2O production was promoted, gasification from the water surface was the most significant emission source, accounting for 52% of the total N2O emitted, on average. The N2O emission factor was often lower than 0.01% during stable operation; however, this factor was subject to sudden increases caused by nitrite accumulation.